ADVANCED PRACTICES IN PALLIATIVE CARE - de Araújo Porto, Virginia; dos Santos Vieira, Débora; França da Silva, Érica; Victor Assis Eloy, Allan; Felix da Silva, Tarciana; Lucas Lopes, Cecília; Ellen Costa Vasconcelos, Eduarda; Miranda Ribeiro de Melo, Andréa; Tatiane Freira, Wilma (Advanced Studies on Health and Nature, 2023)
Health care with a holistic view is essential, targeting the patient in an integral way, meeting their anxieties in the face of the disease, involving physical, psychological, social and spiritual support. In addition, the family’s participation during the therapeutic process of palliation is of great importance, since it directly contributes to the patient’s mood and morale in this difficult diagnosis: having an intractable disease. Among the support measures developed, it is worth mentioning the need to carry out an impeccable assessment identifying the level of pain, stressful symptoms and the evolution of the disease. It is observed that this care can be offered at different levels of complexity, in advanced stages surgical and chemotherapy treatment is essential for symptom control.